1994
DOI: 10.3138/cbmh.11.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Writing Nursing History in Canada: Issues and Approaches

Abstract: Should the history of nursing be presented as part of medical history? Twenty years ago the answer would have been “yes.” Nurses writing about their collective past shared with physician-historians an interest in questions of professionalization, elite institutions (especially hospitals), higher education, dynamic and respected leaders, and interpretive frameworks that often affirmed the profession’s achievements. For these reasons, nursing was often treated as a subset of medicine, an important, although ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Despite purported advancements in the education and practice foundations of both medicine and nursing, there remains an undercurrent of misogynistic domination within the acute care professional culture that is reflected in persistently hierarchical relationships and role distinctions of nurses and physicians (Binnie, 2000; Cowin & Jacobsson, 2003; Duchscher, 2001; Hanmer, 1990; Kimball & O’Neil, 2002; Turner & Colin, 1995). Several authors have suggested that the continued structuring of hospital nurses into traditional gender‐prescribed roles with physicians is motivated by a desire to assure task‐ordered subservience among nurses (Boutilier, 1994; Davies, 2003; Jones, 2003; LeTourneau, 2004; McPherson & Stuart, 1994; Passau‐Buck & Jones, 1994; Turner & Colin, 1995). In a recent study of the impact of nurse–physician relationships within hospitals on nurse satisfaction and retention, an alarming 93% of respondents (which included both physicians and nurses) had witnessed disruptive behavior by physicians in the clinical environment (Rosenstein, 2002).…”
Section: Oppression In Nursingmentioning
confidence: 99%
“…Despite purported advancements in the education and practice foundations of both medicine and nursing, there remains an undercurrent of misogynistic domination within the acute care professional culture that is reflected in persistently hierarchical relationships and role distinctions of nurses and physicians (Binnie, 2000; Cowin & Jacobsson, 2003; Duchscher, 2001; Hanmer, 1990; Kimball & O’Neil, 2002; Turner & Colin, 1995). Several authors have suggested that the continued structuring of hospital nurses into traditional gender‐prescribed roles with physicians is motivated by a desire to assure task‐ordered subservience among nurses (Boutilier, 1994; Davies, 2003; Jones, 2003; LeTourneau, 2004; McPherson & Stuart, 1994; Passau‐Buck & Jones, 1994; Turner & Colin, 1995). In a recent study of the impact of nurse–physician relationships within hospitals on nurse satisfaction and retention, an alarming 93% of respondents (which included both physicians and nurses) had witnessed disruptive behavior by physicians in the clinical environment (Rosenstein, 2002).…”
Section: Oppression In Nursingmentioning
confidence: 99%
“…As McPherson and Stuart (1994) argued, certain groups within nursing have historically been more likely to leave records, which "has often skewed the historical record toward the elite, formally trained, full-time practitioners, and has oriented the record toward the socially respectable or celebratory, leaving more marginal practitioners silent" (p. 16). Paralleling this critique, Flynn started her 2008 history of Black Canadian nurses by stating that "the paucity of historical materials on Black Canadian women does not necessarily mean the sources are unavailable," and went on to describe her use of diverse sources, such as oral interviews, immigration records, and a re-examination of existing archival sources such as yearbooks, syllabi, and conference papers to reveal this history.…”
Section: The Need To Also Look Backwardsmentioning
confidence: 99%
“…from the hospice activities of Hospitaller Knights during the Crusades in the 11th century (Nicholson, 2001). This practice in turn influenced the health oriented activities of European Religious Orders in the late Middle Ages and Renaissance (McPherson & Stuart, 1994), and was subsequently transposed to the New World in the 16th/17th century (Young & Rousseau, 2005). Nursing therefore, existed in parallel with the professional advancements of other knowledge based disciplines.…”
Section: Has Nursing Evolved As a Profession Over Time?mentioning
confidence: 99%